Endoscopic Excision of Supracondylar Humeral Spur for Decompression of the Median Nerve and Brachial Artery - Bain, Gregory (Arthrosc Tech, 2016)
The humeral supracondylar process and Struthers ligament comprise a relatively rare but well-known anatomic variant. They are usually asymptomatic but may produce clinical symptoms related to compression of the median nerve or brachial artery below the ligament. Previously, surgery has been performed with an open ligament release and supracondylar process excision. This article reports on the use of endoscopic findings and the method of ligament release and process excision. Endoscopy is a minimally invasive technique that provides excellent visualization and enables the surgeon to perform dissection with magnification and precision. It allows the surgeon to introduce open surgical techniques into the depths of the wound in a controlled manner. Because of the dead space created, there is a risk of hematoma formation. Many of the concepts used in open surgery are now being used for endoscopic surgery, and vice versa. The barriers and differences among endoscopic, arthroscopic, and open procedures are being broken down. We report another endoscopic technique, which is part of the ongoing evolution of musculoskeletal surgery.